Working Capital Management and Financial Performance: Evidence from Deposit Money Banks in Nigeria - Gbadebo, Adedeji Daniel (Ilomata International Journal of Tax and Accounting, 2024)
Introduction: Clear and well-defined policies regarding working capital management are imperative for organizations. The efficient management of working capital not only enhances a bank's financial performance but also fosters customer confidence, facilitates the payment of short-term debts, and contributes to sectoral growth and national development The paper examines the impact of working capital management on the financial performance of Listed deposit money banks in Nigeria Method: To establish the aim, the paper applies the panel generalized method of moments on published data of deposit money banks in Nigeria from 2012 to 2022. The study uses variables such as working capital, gross operating profit, and cash conversion cycle, as components of working capital management and return on assets to represent financial performance. Result: The outcome shows a positive and significant relationship between effective working capital management and financial performance. The gross operating profit was found to have a positive and significant impact on the financial performance of the banks. The paper identifies a negative but significant relationship between the cash conversion cycle and financial performance. Lastly, the macroeconomic factors, such as inflation rates, and interest rates, were found to have a significant impact on the financial performance of the banks. Conclusion: The study highlights the importance of effective working capital management, and strategic responsiveness to macroeconomic conditions for the financial success of listed deposit money banks in Nigeria. The paper offers, amongst others, that there should be regular assessments of financial performance and internal processes are essential to identify areas of improvement and ensure adherence to best practices in working capital management.